Effect of magnetic field on the hydrogen evolution activity using non-magnetic Weyl semimetal catalysts - Gupta, Uttam; Rajamathi, Catherine R.; Kumar, Nitesh; Li, Guowei; Sun, Yan; Shekhar, Chandra; Felser, Claudia; Rao, C. N. R. (Dalton Transactions, 2020)
An external switch to control the kinetics of the reaction by manipulating the participating electrons could be interesting as it can alter the rate of the reaction without affecting the reaction pathway. The magnetic field, like a switch, is non-invasive, tunable, and clean; it can also alter the electrons in a material. We study the effect of an applied magnetic field on the hydrogen evolution activity of the NbP family of Weyl semimetals because of their extremely high mobility and large magnetoresistance at room temperature and good hydrogen evolution properties. We find that by applying a magnetic field of ∼3500 G, the hydrogen evolution activity of NbP increases by up to 95%. The other members of this Weyl semimetal family (viz. TaP, NbAs, and TaAs) also exhibit increased hydrogen evolution activity. Thus, our observations suggest an interplay of electronic property, magnetic field, and catalytic activity in this class of compounds, providing evidence of manipulating the catalytic performance of topological materials through the application of a magnetic field.
CRIS-Team Scopus Importer:2022-04-14